Synthesis and Micellization of Thermo/pH-Responsive Block Copolymer Poly(2-(diethylamino)ethylmethacrylate)-block-poly(N-isopropylacrylamide) Prepared via RAFT Polymerization - Wu, Chenglin; Ying, Anguo; Ren, Shibin; Xu, Jiankang (Asian Journal of Chemistry, 2013)
Double hydrophilic block copolymer, poly[2-(diethylamino)ethyl methacrylate]-block-poly(N-isopropylacrylamide), PDEAEMA-b-PNIPAM, was successfully synthesized with good control via reversible addition fragmentation chain transfer radical polymerization (RAFT) with 4-cyanopentanoic acid dithiobenzoate (CPADB) as chain transfer agent in 1,4-dioxane. The diblock copolymer forms core-shell micelles in aqueous solution in dependence of pH and temperature. The behaviour of the double responsive block copolymer in solution was investigated by 1H NMR and UV-visible. Cloud points measurements indicated that the the lower critical solution temperature (LCST) of poly(N-isopropylacrylamide) segment was decreased with increasing pH value of the solution, whereas the pKa value of PDEAEMA segment was about pH 7.5.